Speech Acts and their Constructive Roles in Trump’s Argumentation - Al-Ebadi, Hani K.; Kadhim, Hayat Hasan; Murdas, Saad Abdullah (International Journal of Psychosocial Rehabilitation, 2020)
Speech acts perform a central role in fulfilling the argumentative objectives in the argumentative discourse. This is so because of its contribution in forming the argumentative structure of the discourse. This motivates the current study to investigate the role of speech acts and their constructive roles in the American President’s, Trump, argumentative speech in Saudi Arabia 2017 in his attempt to satisfy his argumentative objectives. The study adopts the Pragma-dialectic approach of argumentation (Van Eemeren and Grootendorst, 1983 and Van Ree, 2009) and speech act theory (Searle, 1969; Vanderveken, 1989 and Harnish, 1994) as its model for analyzing the collected data. Some conclusions have been arrived at validating the hypotheses of the study.